2016
DOI: 10.26582/k.48.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of augmented verbal and visual feedback on efficiency in skiing teaching

Abstract: The aims of this study were to analyse the effect of two feedback types as strategies in training ski teachers and to verify their effectiveness in the students’ learning. Thirty ski teachers participated in the study (average age=32.0±5.4 years; average experience in ski teaching=10.0±3 years). The teachers were divided into two experimental groups (group I: verbal feedback; group II: visual and verbal feedback) and one control group. Fifteen teaching trials were performed by each teacher, and a subsequent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The greater improvement in student performances in the combined AF group aligns with the findings of Giannousi et al (2017), who concluded that combining visual and audio feedback was more effective than verbal feedback and traditional teaching when learning freestyle swimming for the first time. Moreover, Martinez et al (2016) demonstrated that immediate visual feedback provided through a portable computer, complemented, and enhanced the verbal feedback as a strategy for training ski instructors. As mentioned by Sigrist, Rauter, Riener, and Wolf (2013a), while visual feedback has the potential to teach complex movements, haptic feedback is suited for teaching temporal aspects of a specific movement.…”
Section: Learning Effects Of Afmentioning
confidence: 99%
See 2 more Smart Citations
“…The greater improvement in student performances in the combined AF group aligns with the findings of Giannousi et al (2017), who concluded that combining visual and audio feedback was more effective than verbal feedback and traditional teaching when learning freestyle swimming for the first time. Moreover, Martinez et al (2016) demonstrated that immediate visual feedback provided through a portable computer, complemented, and enhanced the verbal feedback as a strategy for training ski instructors. As mentioned by Sigrist, Rauter, Riener, and Wolf (2013a), while visual feedback has the potential to teach complex movements, haptic feedback is suited for teaching temporal aspects of a specific movement.…”
Section: Learning Effects Of Afmentioning
confidence: 99%
“…Fredenburg , Lee, and Solmon (2001) have demonstrated that informational feedback is important in facilitating student engagement, fostering positive perceptions of ability, and ultimately, improving performance on challenging tasks. Recently, Martinez, Go´mez-Lo´pez, Femia, Mayorga-Vega, and Viciana (2016) established a model of relevant feedback criteria, including specificity, affectivity, direction, objective, positioning, channeling, timing, comprehension, and precision. Depending on how AF is delivered, it can contribute to building trust and healthy communication between teachers and students, both of which are essential factors in teaching-learning efficiency (Carpentier & Mageau, 2013;Jowett & Cockerill, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skilled movement is fundamental for success across many activities, however, the learning of such movements can be impacted by numerous conditions. Factors, such as amount of practice, type of feedback, practice schedule [1], specificity, positioning, and timing [2], are all vital in skill acquisition. However, it is perhaps more important to understand how to optimize learning, as well as identify factors associated with the acquisition and retention in motor learning [3].…”
Section: Introductionmentioning
confidence: 99%
“…A su vez, la información que se le brinda al participante puede estar enfocada en los errores cometidos -resaltando un mal desempeño-o en los aciertos -basada en el buen desempeño- (16). Para este tipo de feedback, se ha encontrado que el feedback positivo (enfocado en aciertos) es más efectivo (16,36,37) Otra característica relevante del feedback, es el sentido involucrado para hacer llegar la información, entre ellos se encuentra el feedback visual (13)(14)(15)25), el feedback auditivo o verbal (15,38), el feedback táctil(15,39) y el biofeedback (7); o una mezcla de varios sentidos (15,40). El biofeedback es considerado un tipo de feedback aumentado que se origina de respuestas físicas al realizar diferentes tareas, como por ejemplo la frecuencia cardiaca, actividad muscular o cerebral y nivel de consumo de oxígeno (7).…”
Section: Introductionunclassified